Bimetallic Ni‒Co phosphide nanosheets self-supported on nickel foam as high-performance electrocatalyst for hydrogen evolution reaction. (10th September 2019) - Yu, Chen; Xu, Fei; Luo, Lin; Abbo, Hanna S.; Titinchi, Salam J.J.; Shen, Pei Kang; Tsiakaras, Panagiotis; Yin, Shibin
Abstract: In this work, bimetallic nickel-cobalt phosphide (Ni-Co-P/NF) self-supported on nickel foam (NF) is synthesized for hydrogen evolution reaction (HER). A two-step method of electrodeposition with subsequently low-temperature phosphatizing is adopted. The physicochemical characterizations of the as-prepared Ni-Co-P/NF show that the surface is covered by metallic phosphide compounds (NiCoP, NiP and Co2 P) with unique morphology, consisted of nanosheets randomly dispersed on villiform 3D integrated framework. The electrochemical characterizations demonstrate that Ni-Co-P/NF exhibits the highest performance for HER, in 1.0 M KOH aqueous solution, compared to other as-prepared electrocatalysts. Specifically, it requires very low overpotential values of 85, 210 and 350 mV for delivering large current densities of −10, −500 and −1, 500 mA cm −2, respectively, revealing a low Tafel slope of 46 mV dec −1 . Besides, Ni-Co-P/NF also displays long-term durability lasting 24 h without obvious deactivation. This work highlights that the NiCoP, NiP and Co2 P active phases play a crucial role for the good HER activity. In addition, the unique morphology with self-supported structure provides large electrochemical surface area, allowing the exposure of higher amount of active sites for HER. These self-supported electrocatalysts, without binder, could also improve the electrode's HER activity and stability. This work, therefore, provides a controllable and feasible strategy to synthesize bimetallic phosphides of unique morphology with high HER activity. Graphical abstract: Image 1 Highlights: A feasible strategy to fabricate cost-effective Ni-Co-P/NF electrocatalyst is proposed. The presence of multiphases and nanosheets improve HER catalytic performance and stability. Large current densities at −300 and −1500 mA cm −2 require low overpotentials of 210 and 350 mV.